Mini craniotomy for chronic subdural haematoma: surgical outcome from a single institution experience and predictors of success - Hossain, Mohammad Nazrul; Rashid, Mohammad Humayun; Eva, Israt Zerin; Bhuiyan, M. Sharif; Al Mamun, Abdullah (International Journal of Research in Medical Sciences, 2021)
Background: Chronic subdural hematoma (CSDH) is an increasingly common neurological disease in daily neurosurgical practice. Despite the wide prevalence of CSDH, there remains a lack of consensus regarding numerous aspects of its surgical management. The diagnosis and treatment are well established but there are different surgical procedures and outcome related to these procedures are not completely understood. Methods: The study conducted was conducted in department of neurosurgery at Ibrahim cardiac hospital and research institute, Dhaka, Bangladesh between January 2019 to July 2020, 105 patients were treated for chronic subdural haematoma This study evaluated the clinical features, radiological findings and surgical outcome by mini craniotomy assessed by modified Rankin scale (mRS) score and Glasgow outcome scale (GOS) score in a large series of patients treated at single institution. Results: At 6 months follow up, only one patient died (0.95%) because of co-morbidities and not directly related to the chronic subdural haematoma, 15 patients (14.3%) improved to mRS 0, 33.33% showed only mild symptoms without any significant disability-mRS 1, slight disability was observed in 28.5% patients, moderate disability was observed in 17.14% patients-mRS 3, moderately severe disability was observed in 5.7%-mRS 4. Conclusions: GOS score at 6 months follow up which shows majority of the patient improved to GOS score 4 (45.71%) and 5 (38.09%). Based on these results, among various method of surgical management, mini craniotomy provides better outcome.